(untitled) (American Journal of Islam and Society, 1994)
"Are those who know and those who do not know equal!?" (Qur’an 39:9) What we tend nowadays to call "science" in the MITOW or strict sense cove= the latest developments and discoveries in the mathematical, physical, and biological sciences. Yet the expression continues to be used in a wider sense, one that covers our contemporary social sciences and occasionally human Sciences (including perhaps the science of religion) as well. If, when speaking of the Islamic perspective on, or conception of, religious belief, scientific belief, and the relation between them, we mean to’address the entire Islamic tradition, we will invariably be faced with an impossible task. To do this successfully, we would have to start from the Qur’an and go through Islamic history century by century, if not generation by generation, and see how the Qur’anic perspective was realized by the Muslim community in diverse regions and disciplines. This process would reveal what tensions and conflicts arose, how these were resolved, and what happened when the Muslim world was faced with the adoption of what we now call "science." Putting this task aside, we can perhaps touch on a few points in that long and complex history. First of all, we will speak briefly of the Qur’anic perspective and then say a few words about how the different sciences, when developed, were organized into a general scheme of human knowledge and how this organization implies a certain view of the relation between religious belief and scientific belief. This talk will conclude with the raising of some questions regarding what we understand by the term "Islamic science" when we use it as a historical or classificatory notion. The Qur’anic Perspective The Arabic expressions in the Qur’an that are used to signify mental discipline and usually translated into English as "science" are primarily two: ’ilm, normally rendered as "science" or "knowledge" (a faculty of sciences is regularly called kulhyat al ’ulum in Arabic, ’ulum being the plural of ’ilm) and &huh, normally tendered as "wisdom." To begin ...